The applicability of elastic garment therapy in children with cerebral palsy (Research, Society and Development, 2022)
Introduction: Cerebral Palsy (CP) is defined as a chronic non-progressive encephalopathy that occurs due to a lesion in the developing brain, compromising motor functions and posture. Through several protocols, including the Pediasuit and Therasuit, with the main therapeutic objective of promoting the training and development of neuromotor functions. Objective: to describe the therapeutic effects produced by the Pediasuit and Therasuit methods in children with CP. Methodology: This is a systematic review, carried out in the electronic databases SciELO, LILACS, PubMed and CAPES Periodicals, in English, Portuguese and Spanish. As a search strategy, the keywords cerebral palsy, elastic clothing, pediatric suit, therasuit, intensive neuromotor therapy, were used, in combination oral one. Result: Upon identifying about 21,116 articles, these were submitted to the inclusion and exclusion criteria, leaving about 28 articles for the composition of this article. Conclusion: Although there are few articles that directly address the Pediasuit and Therasuit methods in children with CP, the existence of gaps that need to be answered in future research is identified, through a control group, comparisons of techniques and the potential effectiveness of the aforementioned methods, although it makes us identify the existence of positive gains in child development, aimed at advances motors and postures.